Chemical composition, antimicrobial and cytotoxic activities of Piper hispidum Sw. essential oil collected in Venezuela - Antonio Moralesa, Janne Rojasa, Laila M. Moujirb, Liliana Araujob and María Rondónc (Journal of Applied Pharmaceutical Science, 2013)
This article provides an evaluation of the chemical composition, antimicrobial and cytotoxic activities of the essential oil of Piper hispidum Sw collected in the Venezuelan Andes. The chemical composition was examined by GC/MS analysis. Thirty four compounds were identified representing 95.2 % of the total oil. The major components were α-pinene (15.3 %), β-pinene (14.8 %), β-elemene (8.1 %), caryophyllene oxide (7.8 %) and δ-3-carene (6.9 %). Antimicrobial activity was observed against Gram positive bacterial strains S. aureus ATCC 6538, S. epidermides CECT232, S. saprophyticus CECT 235, B. cereus CECT496, B. subtilis CECT39 and E. faecalis CECT735 showing MIC values between 6.25 to 15 μg/mL and MBC values of 12.5 to 15 μg/mL however a low activity was observed against Gram negative bacterial strains E. coli CECT99, P. mirabilis CECT 170 and P.aeruginosa AK 958 performing MIC and MBC values of > 200 μg/mL. On the other hand, Candida albicans yeast presented a moderate activity with MIC 100-200 µg/mL and MBC > 200 μg/mL.Cytotoxic activity was also determined against HeLa (cervix carcinoma), A-459 (lung carcinoma), MCF-7 (breast adenocarcinoma) human cancer cell lines and against normal Vero cells (African green monkey kidney), exhibiting potent antiproliferative effects with IC50 values ranging from 18.6 to 37.7 µg/mL.
Keywords: Piper hispidum, essential oil, an